Chlamydia trachomatis infection among Ghanaian women undergoing hysterosalpingography for suspected tubal factor infertility. Issue 2 (19th June 2019) - Beyuo, Titus; Oppong, Samuel A.; Samba, Ali; Beyuo, Vera M.
Abstract: Objective: To determine the prevalence of Chlamydia trachomatis infection and the correlates of tubal pathology among Ghanaian women undergoing hysterosalpingography for suspected tubal factor infertility. Methods: A cross‐sectional study was conducted among 189 women with infertility who underwent hysterosalpingography at Korle Bu Teaching Hospital, Ghana, from September 1 to November 30, 2016. Demographic data; obstetric and gynecologic history; and hysterosalpingography findings were collected using a structured questionnaire. Endocervical swabs were tested for the presence of Chlamydia trachomatis using a rapid antigen‐based diagnostic kit. Associations between the variables were assessed using bivariate analysis. Results: Positive test results for Chlamydia trachomatis were recorded among 15 participants, giving an overall prevalence of 7.9% (95% confidence interval [CI] 4.1%–11.7%). In all, 67 (35.4%) participants had abnormal findings on hysterosalpingography, with 40 (21.2%) displaying bilateral tubal occlusion. The remaining 122 (64.6%) women had normal findings on hysterosalpingography. Eight participants with normal tubal appearance tested positive for Chlamydia trachomatis (prevalence 6.6%, 95% CI 2.2%–11.0%), whereas seven participants with abnormal tubal appearance tested positive (prevalence 10.4%, 95% CI 3.1%–17.7%; P =0.402). No associations were found between participant characteristics and tubal pathology. Conclusion: The prevalence of Chlamydia trachomatis did not differ by hysterosalpingography findings. Abstract : The overall prevalence of Chlamydia trachomatis was 7.9%, with rates of 6.6% and 10.4% recorded among women with or without tubal pathology on hysterosalpingography.